Digital (AI-Based) Education Management in Enhancing Teacher Professionalism: A Multisite Study at the UPT Elementary Education Unit of SDN Tlogobodosari I, Pasuruan - SUYAT, MOCH.; Ahmad Thohirin; A. Faizin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The era of the Industrial Revolution 4.0 and Society 5.0 demands digital transformation in the education sector. This study aims to develop a model and implementation strategies for artificial intelligence (AI)-based educational management to enhance teacher professionalism in elementary schools. The research employed a descriptive qualitative method using a multisite study approach at SDN Tlogobodosari I, Pasuruan. Data were collected through observation, in-depth interviews, and document analysis, and were analyzed using data condensation, data display, and conclusion-drawing techniques. The findings indicate that an AI-based management model integrated with the POAC functions (Planning, Organizing, Actuating, and Controlling) can improve efficiency and personalize teacher professional development. Key success factors include the principal’s digital leadership, an innovative school culture, teachers’ digital competencies, and adequate infrastructural and technical support. This study concludes by providing a practical roadmap for schools in adopting AI for teacher development, as well as theoretical contributions to the fields of digital educational management and technology-based school leadership.